INFLUENCE OF BODY CONDITION ON THE REPRODUCTIVE PERFORMANCE OF THE SOW - Valdez, Juan Manuel Romo; Aguirre, Laura Francisca Espinoza; Gómez, Ignacio Peralta; Loera, Jesús José Portillo; Valdez, Ana Mireya Romo; Romo-Rubio, Javier Alonso (Editora Impacto Científico, 2025)
Backfat thickness (BFT) is an indicator of sow body condition. Maintaining optimal body condition in high-producing sows is important for their performance, reproductive efficiency, and longevity. A BFT between 17 and 22 mm at the end of gestation is associated with larger litter size and piglet birth weight, higher growth rate and piglet weaning weight, and a shorter weaning-to-estrus interval (WEI). Furthermore, it is associated with fewer piglets with intrauterine growth restriction (IUGR) and with a linear increase in BFT gain from weaning to day 109 of the following gestation. Therefore, it is recommended that nulliparous and multiparous sows have a BFT between 15 and 18 mm at breeding. A low BFT delays the onset of puberty. In this regard, leptin and insulin-like growth factor I (IGF-I) have been observed to be associated with BFT and age at puberty. Likewise, a low BFT has been associated with lower litter size and growth, as well as prolonged WEI. A very high BFT (>26 mm) has been associated with less mammary development, potentially translating into lower milk production and litters with lower weight gain during lactation. Excessive feed intake during early gestation should be avoided, as it increases embryonic mortality in gilts and decreases feed intake during lactation. Evidence indicates that an BFT less than 15 mm or greater than 26 mm at the end of gestation may affect the sow's reproductive performance.DOI: https://doi.org/10.56238/edimpacto2025.073-001